Modelování konkurenceschopnosti regionů v podmínkách globalizace - Provazníková, Romana; Křupka Jiří; Kašparová, Miloslava (Univerzita Pardubice, 2009)
The article analyzes regional competitiveness with the utilization of nonhierarchical cluster analyzes. Used indicators for the definition of regional competitiveness, both on the national level and on the regional level - NUTS 2 Cohesion region are presented. For the creation of the model six indicators defined on the NUTS 2 regions in selected "new" European Union member states have been selected. The created model allows for deeper and more complex view on the grouped regions according to the selected indicators between NUTS 2 regions in various countries.
Keywords: regional competitiveness indicators; NUTS 2 region; matrix of competitiveness; Cluster Analysis